APPLICATION OF A COMBINATION OF RANGE OF MOTION (ROM) AND HEAD OF BED (HOM) ELEVATION IN ISCHEMIC STROKE PATIENTS WITH PHYSICAL MOBILITY IMPAIRMENT IN SURABAYA HOSPITAL: A CASE STUDY - Yayuk Ernawati; Yurike Septianingrum; Lono Wijayanti; Umdatus Soleha (Literasi Kesehatan Husada, 2025)
Background: Stroke patients often experience hemiplegia or hemiparesis. Proper treatment can help the healing and recovery process.